Highly Efficient Photosensor Based on Reduced Graphene Oxide - Gupta, R. K.; Alahmed, Z. A.; Albrithen, H. A.; Yakuphanoğlu, Fahrettin (Amer Scientific Publishers, 2014)
In this article, a photo sensor based on reduced graphene oxide (RGO) and p-silicon has been fabricated. The structural property of the synthesized AGO was confirmed using X-ray diffraction and Fourier transform infrared spectroscopy. The presence of (002) peak in the X-ray diffraction patterns of AGO at 10.63 degrees indicates that graphite was exfoliated. The current voltage characteristics of the diode were examined under dark and different light intensities. The device shows good rectification behavior. The junction parameters including ideality factor and barrier height were determined. Our results indicate that photocurrent of the diode depends not only on voltage but also on the light intensity. Additionally, the transient photo-current, capacitance, and conductance measurement were performed, and it was found that these properties highly depend on light intensity. The present study suggests that AGO has high potential for photosensor applications.
Keywords: Reduced Graphene Oxide; Schottky Diode; Photodiode; I-V Characteristics